The Flintstones. The complete first season The complete first season - Reed, Alan, 1907-1977.; Vander Pyl, Jean, 1919-1999.; Blanc, Mel.; Benaderet, Bea, 1906-1968.; Stephenson, John, 1923-; Smith, Hal, 1916-1994.; Barbera, Joseph; Hanna, William, 1910-2001.; Hanna-Barbera Productions; Screen Gems. (Burbank, CA : Warner Home Video, 2004)
From the town of Bedrock, modern stone-age family Fred and Wilma Flintstone and their goofy best-friends and neighbors Barney and Betty Rubble comically trudge through prehistoric daily lives.
disc 3. Girls' night out -- Arthur Quarry's dance class -- Big bank robbery -- Snorkasaurus hunter -- Hot piano -- Hypnotist -- Love letters on the rocks -- disc 4. Tycoon -- Astra' nuts -- Long long weekend -- In the dough -- Good scout -- Rooms for rent -- Fred Flintstone, before and after.
Collective title from container.
Originally produced as episodes of the television program The Flintstones in 1960 and 1961.
Special features: all about the Flintstones, chronicles the history of the series; wacky inventions featurette; the Flagstones, the lost episode; early TV commercials; network promo spots.
Animation director, Charles A. Nichols ; editor, Donald A. Douglas ; music, Hoyt S. Curtin ... [et al.] ; character designer, Ed Benedict.
Voices: Alan Reed, Jean Vanderpyl, Mel Blanc, Bea Benaderet, John Stephenson, Hal Smith.
Not rated
Keywords: Flintstones (Fictitious characters) -- Drama; Stone age -- Drama; Family -- Drama; Television programs for the hearing impaired